A molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material and its preparation method and application

The Ag3PO4/TiO2 photocatalytic film material prepared by molecular imprinting technology solves the problems of easy agglomeration, poor activity and poor selectivity of existing photocatalytic materials, achieves efficient and highly selective photocatalytic degradation effects, and promotes the recycling and utilization of materials.

CN116273086BActive Publication Date: 2025-04-22SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211666112.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-04-22
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

Existing photocatalytic materials are prone to agglomeration, poor photocatalytic activity and poor degradation selectivity, which limit their application and industrialization in complex pollution systems.

Method used

Ag3PO4/TiO2 photocatalytic film material was prepared by molecular imprinting technology, and a molecular imprinting structure was formed through hydrolysis-condensation reaction and hydrothermal treatment, and supported on a transparent support to form a photocatalytic film material that is not easy to agglomerate.

Benefits of technology

The specific surface area of ​​the material and the contact site of the photocatalytic reaction are improved, the selective degradation capacity of the target object is enhanced, the photocatalytic degradation efficiency is significantly improved, and the material is easy to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273086B_ABST
    Figure CN116273086B_ABST
Patent Text Reader

Abstract

The present invention relates to a molecular imprinted Ag3PO4 / TiO2 photocatalytic film material, a preparation method and an application. The preparation method of the material comprises the following steps: S1. dissolving a molecular template and a titanium source in a solvent, causing a hydrolysis-condensation reaction, then sequentially adding a silver source solution and a phosphate, stirring, performing a hydrothermal reaction at 120-200°C for 16-24h, and calcining to obtain molecular imprinted Ag3PO4 / TiO2; S2. loading the molecular imprinted Ag3PO4 / TiO2 on a transparent carrier. The molecular imprinted Ag3PO4 / TiO2 photocatalytic film material prepared by the preparation method is not easy to agglomerate, increases the specific surface area and the contact sites of the photocatalytic reaction, and at the same time effectively solves the problem of the selectivity of the material for the degradation of the target object, and also improves the ability of the material to target adsorption and enrichment in a complex system, and significantly improves the photocatalytic degradation efficiency of the target object.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and more specifically, to a molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material and a preparation method and application thereof. Background Art

[0002] Photocatalytic technology is a new technology that uses ultraviolet light or sunlight for energy conversion and environmental purification. It has the advantages of high efficiency, safety, low consumption, and wide application, and has attracted much attention in many fields.

[0003] Titanium dioxide (TiO2) is the most active and widely studied semiconductor photocatalyst. Its advantages such as high refractive index, commercial availability, non-toxicity, photostability and suitable electronic band structure give it great potential application value in organic wastewater treatment, gas purification, sterilization and deodorization. At present, people are studying various modification methods to improve the photocatalytic performance of TiO2, targeting its inherent defects such as high band gap energy (3.2eV), low light absorption and utilization ability (>397nm), and high recombination efficiency of photogenerated carriers. Silver phosphate (Ag3PO4) is a new type of photocatalyst with a band gap of about 2.38eV, a quantum efficiency of up to 90% in the visible light region, and better photocatalytic oxidation performance than TiO2. However, Ag3PO4 has the disadvantage of high recombination rate of photogenerated electron-hole pairs of traditional photocatalysts; due to its photosensitivity and solubility in water, it is easily corroded by light during the photocatalytic reaction, and its poor stability leads to high synthesis cost, which limits its practical application. In order to improve the stability of Ag3PO4, it needs to be modified. Ag3PO4 and TiO2 form a pn-type staggered heterojunction structure, which can provide an effective migration interface for photogenerated electron-hole pairs, achieve high-efficiency photogenerated carrier separation efficiency, and enhance the spectral response range, and can exhibit excellent chemical stability and photocatalytic oxidation performance under visible light.(Wang H,Wang L,Ye S,etal.Construction of Bi2WO6-TiO2 / starch nanocomposite films for visible-lightcatalytic degradation of ethylene[J].Food Hydrocolloids,2018,88:92-100;WangR,Xu M,Xie J,et al.A spherical TiO2-Bi2WO6composite photocatalyst for visible-light photocatalytic degradation of ethylene[J].Colloids and Surfaces A:Physicochemical and Engineering Aspects,2020,602:125048;Wang Z,Hu T,Dai K,etal.Construction of Z-scheme Ag3PO4 / Bi2WO6 composite with excellent visible-light photodegradation activity for removal of organic contaminants[J].Chinese Journal of Catalysis, 2017, 38: 2021-2029; Ma Xifeng. Preparation and photocatalytic performance of Ag / Ag3PO4 / TiO2 double heterojunction catalyst [J]. Chemistry and Bioengineering, 2021, 38(10): 37-40).

[0004] However, although photocatalytic materials have been widely used in the degradation of various organic pollutants in water bodies, these materials are generally nanopowder materials, which are easy to agglomerate and difficult to recycle in the water phase. In addition, since these photocatalytic materials themselves have almost no selectivity, it is difficult to effectively degrade highly toxic and low-concentration organic pollutants in complex pollution systems. In the actual degradation application of organic pollutants, it is often necessary to achieve the purpose of preferential degradation of specific pollutants by photocatalytic materials. Therefore, the selectivity of traditional photocatalytic materials for degrading organic matter is poor, which limits the actual industrial application of photocatalytic materials.

[0005] Therefore, developing a photocatalytic material with good dispersibility, good photocatalytic activity and good degradation selectivity is of great significance and application value. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problems of easy agglomeration, poor photocatalytic activity and poor degradation selectivity of the above-mentioned existing photocatalytic materials, and to provide a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material. The molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material prepared by the preparation method is not easy to agglomerate, and the specific surface area and the contact sites of the photocatalytic reaction are increased. At the same time, the molecular imprinting technology enables the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material to not only effectively solve the problem of the selectivity of the material for the degradation of the target object, but also improve the material's ability to target adsorption and enrichment of the target object in a complex system, integrating specific selection, adsorption and photocatalytic functions, maximizing the synergistic effect, and significantly improving the photocatalytic degradation efficiency of the target object. In addition, since the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material is not easy to agglomerate, it is easy to recycle and can be recycled and reused.

[0007] A further object of the present invention is to provide a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material.

[0008] A further object of the present invention is to provide the use of the above molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material in degrading antibiotics or organic pollutants in food.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material comprises the following steps:

[0011] S1. The molecular template and titanium source are dissolved in a solvent to undergo a hydrolysis-condensation reaction, and then a silver source solution and a phosphate are added in sequence, stirred, and subjected to a hydrothermal reaction at 120-200°C for 16-24h, and calcined to obtain molecularly imprinted Ag3PO4 / TiO2;

[0012] S2. The molecularly imprinted Ag3PO4 / TiO2 is loaded on a transparent carrier to obtain the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material;

[0013] In step S1, the molecular template is sulfadimethoxine, the molar ratio of the molecular template to the titanium source is (4-10):1; the volume ratio of the titanium source to the silver source solution is 1:(1-5);

[0014] The number of supported layers of the molecular imprinted Ag3PO4 / TiO2 in step S2 is 2 to 8 layers.

[0015] The preparation method of the invention uses sulfadimethoxine as a molecular template, firstly adds the molecular template and a titanium source in a specific molar range ratio, and the titanium source undergoes a hydrolysis-condensation reaction to form a molecular imprinting polymer material. The polymer material prepared by the molecular imprinting technology can completely match the target molecule in spatial structure and recognition site, and has the ability of specific recognition and identification; then, a silver source solution and a phosphate are added, and molecular imprinting Ag3PO4 / TiO2 is obtained through a specific hydrothermal reaction, calcination, etc., and then the molecular imprinting Ag3PO4 / TiO2 is loaded on a transparent carrier to realize the immobilization of the molecular imprinting Ag3PO4 / TiO2, that is, the molecular imprinting Ag3PO4 / TiO2 photocatalytic thin film material is obtained.

[0016] The present invention adopts molecular imprinting technology to prepare molecular imprinted Ag3PO4 / TiO2 and loads it on a transparent carrier to obtain a molecular imprinted Ag3PO4 / TiO2 photocatalytic film material, which is not easy to agglomerate, increases the specific surface area and the contact sites of the photocatalytic reaction, and at the same time, the molecular imprinting technology enables the molecular imprinted Ag3PO4 / TiO2 photocatalytic film material to not only effectively solve the problem of the selectivity of the material for the degradation of the target object, but also improve the ability of the material to target adsorption and enrichment in a complex system, integrate specific selection, adsorption and photocatalytic functions, is not easy to agglomerate and is easy to recover, maximizes the synergistic effect, and significantly improves the photocatalytic degradation efficiency of the target object. The molecular imprinted Ag3PO4 / TiO2 photocatalytic film material can be widely used in the field of food, especially, it is used to degrade sulfadimethoxine in milk, the degradation rate can reach 67-82%, and the catalytic degradation activity is excellent.

[0017] Preferably, the molar ratio of the molecular template to the titanium source in step S1 is (6-10):1.

[0018] More preferably, the molar ratio of the molecular template to the titanium source in step S1 is (6-8):1.

[0019] Preferably, the mass ratio of the silver source to the phosphate in the silver source solution in step S1 is 1:(1.9-2.1).

[0020] Preferably, the mass fraction of the silver source in the silver source solution in step S1 is 0.8-1.2%.

[0021] Preferably, the specific process of the hydrolysis-condensation reaction is: dissolving the molecular template and the titanium source in a solvent, and then adding an ethanol aqueous solution of glacial acetic acid.

[0022] Preferably, the stirring condition in step S1 is: stirring for 3 to 4 hours at a pH of 2 to 3.

[0023] Preferably, the conditions of the hydrothermal reaction in step S1 are: reacting at 160-180° C. for 20-24 hours.

[0024] Preferably, after the hydrothermal reaction and before calcination in step S1, the steps of cooling, washing, drying and grinding are also included.

[0025] Preferably, the calcination conditions in step S1 are: calcination at 400-550° C. for 1.5-3 h.

[0026] Preferably, the calcination in step S1 is carried out in a tubular electric furnace.

[0027] Preferably, the calcination in step S1 further includes washing and drying steps.

[0028] Preferably, the titanium source in step S1 is butyl titanate; the silver source in the silver source solution is AgNO3; and the phosphate is one or more of Na3PO4·12H2O, Na2HPO4·7H2O or NaH2PO4·2H2O.

[0029] Preferably, the loading times in step S2 is 2 to 8 times. Each time the loading is performed, one layer of molecular imprinted Ag3PO4 / TiO2 is loaded. If two layers of molecular imprinted Ag3PO4 / TiO2 are to be loaded, the loading is performed twice, and so on.

[0030] More preferably, the number of loading in step S2 is 4 to 6 times, that is, the number of loaded layers of molecular imprinted Ag3PO4 / TiO2 in step S2 is 4 to 6 layers.

[0031] Preferably, the specific process of the loading in step S2 is: dispersing the molecular imprinted Ag3PO4 / TiO2 in a dispersing solvent to obtain a sol, immersing the transparent carrier in the sol, taking it out, and drying it to complete the loading.

[0032] More preferably, the usage ratio of the molecular imprinted Ag3PO4 / TiO2 to the dispersion solvent is 1 g: (100-200) mL.

[0033] More preferably, the dispersion solvent is water.

[0034] More preferably, a dispersant is also added to the dispersing solvent.

[0035] Further preferably, the dispersant is one or more of polyvinyl pyrrolidone, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide or sodium polyacrylate.

[0036] Further preferably, the amount of the dispersant used is 0.5-2 wt % of the molecularly imprinted Ag3PO4 / TiO2.

[0037] More preferably, the dispersion further includes steps of adjusting pH, stirring and ultrasound.

[0038] More preferably, the pH is 7 to 8, the stirring time is 30 to 50 min, and the ultrasonic condition is 300 to 500 W power for 20 to 40 min.

[0039] Preferably, the transparent carrier is a glass carrier.

[0040] More preferably, the glass carrier is a quartz glass tube.

[0041] More preferably, the transparent carrier is immersed in the sol for 4 to 5 hours, and is dried at a temperature of 75 to 85° C. and for 3 to 5 hours after being taken out.

[0042] A molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material is prepared by the preparation method.

[0043] The application of the molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material in degrading antibiotics or organic pollutants in food is also within the protection scope of the present invention.

[0044] Preferably, the antibiotic is sulfadimethoxine.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The molecular imprinted Ag3PO4 / TiO2 photocatalytic film material is not easy to agglomerate, and the specific surface area and the contact sites of the photocatalytic reaction are increased. At the same time, the molecular imprinting technology enables the molecular imprinted Ag3PO4 / TiO2 photocatalytic film material to not only effectively solve the problem of the selectivity of the material for the degradation of the target, but also improve the material's ability to target adsorption and enrichment of the target in a complex system, integrating specific selection, adsorption and photocatalytic functions, maximizing the synergistic effect, and significantly improving the photocatalytic degradation efficiency of the target. In addition, since the molecular imprinted Ag3PO4 / TiO2 photocatalytic film material is not easy to agglomerate, it is easy to recycle. The molecular imprinted Ag3PO4 / TiO2 photocatalytic film material can be widely used in the food field. In particular, it is used to degrade sulfadimethoxine in milk, and the degradation rate can reach 67-82%, with excellent catalytic degradation activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the SEM image of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of Example 1.

[0048] Figure 2This is the EDS image of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of Example 1.

[0049] Figure 3 The photocatalytic degradation performance of SMZ and its kinetic fitting straight line diagram of molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials prepared at different molar ratios of template molecules (SMZ) and functional monomers (butyl titanate).

[0050] Figure 4 The photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material and the kinetic fitting straight line graph are compared with the dosage ratio of titanium source and silver source.

[0051] Figure 5 The photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials with different loading layer numbers and the kinetic fitting straight line graph.

[0052] Figure 6 This is the SEM image of the non-molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of Comparative Example 1. DETAILED DESCRIPTION

[0053] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0054] Example 1

[0055] This embodiment provides a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material, comprising the following steps:

[0056] 1. Take 10 ml of butyl titanate, a certain mass of template molecule sulfadimethylpyrimidine (SMZ) and 4 ml of glacial acetic acid and dissolve them in 20 ml of anhydrous ethanol, wherein the molar ratio of the template molecule sulfadimethylpyrimidine (SMZ) to the functional monomer butyl titanate is 8:1, stir at room temperature 25 ° C for 1 hour to obtain a uniform and transparent yellow solution, which is recorded as liquid A; take 6 ml of anhydrous ethanol, 6 ml of glacial acetic acid and 4 ml of distilled water in a 250 ml beaker at room temperature, stir magnetically for 1 hour to fully mix, and place in a separating funnel for standby use, which is recorded as liquid B; under rapid stirring, slowly add liquid B to liquid A at a speed of 10 drops / min to obtain a colorless, uniform and transparent sol, and then add 4 0mL of 1wt% silver nitrate solution and 40mL of 2wt% sodium phosphate solution (the mass ratio of silver nitrate to sodium phosphate is fixed at 1:2), after magnetic stirring for 60min, the pH value of the solution is adjusted to 2.5 to form liquid C; after continuing stirring for 3 hours, acetalization reaction occurs to obtain a white hydrogel solution, and a white gel is obtained after aging at room temperature for 12h, which is transferred to the lining of the reactor, hydrothermally reacted at 180℃ for 20h, and naturally cooled to room temperature. The reaction product is collected and centrifuged and washed, washed with anhydrous ethanol and deionized water 3 times each, dried at 70℃, ground into powder, and calcined at 500℃ in a tubular electric furnace for 2h to remove the template molecule SMZ. The calcined product is collected and washed with distilled water 3 times, and then placed in an oven at 60℃ for 10h to obtain molecularly imprinted Ag3PO4 / TiO2 (abbreviated as MAT) powder.

[0057] 2. Use detergent and distilled water to repeatedly clean the surface of a 250 mL cylindrical quartz glass tube for several times, wipe off water droplets with absorbent paper after cleaning; soak the surface of the quartz glass tube with a 1 mol / L NaOH solution for 3 hours, and rinse off the residual liquid with distilled water for several times; then soak the surface of the quartz glass tube with a 40% HF solution for 12 hours, and rinse off the residual liquid with distilled water for several times; finally, soak the quartz glass in an acetone solution, take it out after 4 hours, and rinse it again with distilled water. After the treatment is completed, move the quartz glass to an oven (90°C) for drying to obtain a pretreated quartz glass tube.

[0058] 3. Accurately weigh 1g MAT powder and 0.1g polyvinylpyrrolidone (PVP-k30) in a 250mL beaker, add 150mL distilled water and stir magnetically for 30min, adjust the pH of the solution to 7.5 with HCl (0.1mol / L) and NaOH (1mol / L), stir magnetically for 15min to mix thoroughly, and finally place the solution in an ultrasonic cleaner for 30min to obtain a stable and uniform MAT sol.

[0059] 4. The prepared MAT sol was fully transferred to a 250 mL measuring cylinder, and the pretreated quartz glass tube was completely immersed in the measuring cylinder for 4 hours. Then, while ensuring that the quartz glass tube did not contact the inner wall of the measuring cylinder, it was taken out at a uniform speed and placed in an 80°C oven for drying. The quartz glass tube was rotated horizontally and at a uniform speed until the MAT sol could be evenly and stably loaded on the outer surface of the quartz glass tube. The sol was continued to be dried for 3 hours until the sol was completely dried, and a loading was completed. The number of loaded layers of molecular imprinted Ag3PO4 / TiO2 was one layer. The soaking and drying steps were repeated once more, so that the number of loaded layers of molecular imprinted Ag3PO4 / TiO2 was 2 layers, and the molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material was obtained.

[0060] The molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this embodiment was characterized by field emission scanning electron microscopy (FESEM) to obtain a SEM image, as shown in FIG. Figure 1 As shown; the molecular imprinted Ag3PO4 / TiO2 in the molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material was also tested by an energy dispersive spectrometer (EDS) to obtain an EDS diagram, as shown Figure 2 As shown. Figure 1 It can be seen that the surface of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic film material has a relatively obvious pore structure, indicating that the high-temperature calcination of the template molecules leaves behind micron-scale imprinted cavities. In addition, the surface of the deeper holes is relatively rough, and nanoscale imprinted cavities may be formed inside. It can be seen that these imprinted cavities are not consistent with the SMZ shape and size at the macro level, but match the template molecule SMZ at the micro level in terms of spatial configuration, functional groups, chemical bonds, etc. Many small white particles are attached to the surface of the TiO2 substrate, combined with Figure 2 The distribution ratio of each element in the EDS diagram can infer that the small particles are silver phosphate particles, indicating that Ag3PO4 in the molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material is attached to the TiO2 surface and forms a composite through interface contact. The porous structure of the molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material makes its density smaller and the surface energy higher, further improving the ability to capture the target substrate.

[0061] The molecular imprinted Ag3PO4 / TiO2 photocatalytic film material of the present embodiment was taken for photocatalytic degradation test. The process of photocatalytic degradation test is: the molecular imprinted Ag3PO4 / TiO2 photocatalytic film material is placed in a stainless steel container containing 250mL of milk solution with a concentration of 10mg / L SMZ, stirred for 50min in dark to allow the catalyst to reach adsorption equilibrium (preliminary experiments have shown that adsorption in the dark for 50min is basically in an adsorption equilibrium state), the light source is turned on to irradiate the sample liquid for photodegradation reaction, sampling is performed every 30min, the sample liquid is centrifuged at 8000rpm for 10min, 1ml of supernatant is taken and filtered through a 0.22μm filter membrane, and then stored in a brown vial, and then the concentration is detected by enzyme-linked immunosorbent assay, and then the concentration is calculated according to the Lambert-Beer law, multiplied by the corresponding dilution multiple, and finally the degradation rate is calculated according to the formula. After reacting for 2h under visible light, the degradation rate of SMZ is determined. The degradation rate of the photocatalytic degradation test of the molecular imprinted Ag3PO4 / TiO2 photocatalytic film material of the present embodiment is 82.4%.

[0062] Example 2

[0063] The present embodiment provides a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material. The preparation method of the present embodiment is basically the same as that of Example 1, except that the molar ratio of the template molecule sulfamethoxazole (SMZ) and the functional monomer butyl titanate in step 1 is 6:1, followed by a hydrothermal reaction at 160°C in a reactor for 24 hours, and finally calcined at 450°C in a tubular electric furnace for 2 hours.

[0064] The field emission scanning electron microscopy (FESEM) characterization results of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this example are similar to those of Example 1.

[0065] The molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this embodiment was tested according to the aforementioned photocatalytic degradation test, and the degradation rate was 80.9%.

[0066] Example 3

[0067] The present embodiment provides a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material. The preparation method of the present embodiment is basically the same as that of Example 1, except that: in the first step, 30 mL of 1 wt% silver nitrate solution and 30 mL of 2 wt% sodium phosphate solution (the mass ratio of silver nitrate to sodium phosphate is fixed at 1:2) are added, followed by a hydrothermal reaction at 160°C in a reactor for 24 hours, and finally calcined at 450°C in a tubular electric furnace for 2 hours.

[0068] The field emission scanning electron microscopy (FESEM) characterization results of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this example are similar to those of Example 1.

[0069] The molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this embodiment was tested according to the aforementioned photocatalytic degradation test, and the degradation rate was 77%.

[0070] Example 4

[0071] This embodiment provides a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material. The preparation method of this embodiment is basically the same as that of Example 1, except that: in step 4, four loadings are performed, and the number of loaded layers of the molecularly imprinted Ag3PO4 / TiO2 is 4.

[0072] The field emission scanning electron microscopy (FESEM) characterization results of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this example are similar to those of Example 1.

[0073] The molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this embodiment was tested according to the aforementioned photocatalytic degradation test, and the degradation rate was 75%.

[0074] Example 5

[0075] This embodiment provides a method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material. The preparation method of this embodiment is basically the same as that of Example 1, except that: in step 4, two loadings are performed, and the number of loaded layers of the molecularly imprinted Ag3PO4 / TiO2 is 2 layers.

[0076] The field emission scanning electron microscopy (FESEM) characterization results of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this example are similar to those of Example 1.

[0077] The molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this embodiment was tested according to the aforementioned photocatalytic degradation test, and the degradation rate was 67%.

[0078] Example 6

[0079] 1. The effect of the molar ratio of template molecule (SMZ) to functional monomer (butyl titanate) on the photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials.

[0080] Figure 3The photocatalytic degradation performance of SMZ and its kinetic fitting line of molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials prepared under different molar ratios of template molecules (SMZ) and functional monomers (butyl titanate) under the same other conditions. Figure 3 It can be seen that the photocatalytic degradation reaction of SMZ by molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film materials synthesized at different molar ratios of template molecules to functional monomers conforms to the first-order reaction kinetics, and the fitting effect of each curve is good, indicating that the reaction rate constant Kˊ value can well reflect the effect of molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film materials on the photocatalytic degradation of SMZ; with the increase of the molar ratio of template molecules to functional monomers, the photocatalytic degradation activity of molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film materials shows a trend of first increasing and then decreasing. When the molar ratio is 4:1, the reaction rate constant Kˊ value of molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film materials for the degradation of SMZ is low, which is 0.35×10 -2 min -1 ; As the molar ratio increases, the degradation rate of SMZ increases. When the molar ratio is 8:1, the K value reaches the maximum of 1.2×10 -2 min -1 The degradation rate is as high as 77%. When the molar ratio is 10:1, the K value reaches 0.78×10 -2 min -1 , the maximum degradation rate is 60%. This is because as the amount of template molecules increases, more template molecules can interact with functional monomers through hydrogen bonds. After full reaction, the template molecules are cross-linked in the Ti-O-Ti grid, and more imprinting sites can be formed after high-temperature elution, which is conducive to the adsorption and enrichment of the target substrate during the photocatalytic reaction, thereby increasing the chance of contact with the photocatalyst for photocatalytic reaction; when the amount of template molecules is further increased, the cross-linking solution reaches saturation too early, and the "re-stabilization" phenomenon occurs, which makes some functional monomers unable to be fully utilized, reducing the photocatalytic effect, and too many template molecules cannot independently construct imprinting sites, so the adsorption performance cannot be further improved, resulting in a decrease in the photocatalytic degradation activity of SMZ.

[0081] 2. The effect of the dosage ratio of titanium source and silver source on the photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials.

[0082] Figure 4The following is the effect of the titanium source and silver source dosage ratio (volume ratio of titanium source to 1wt% silver nitrate solution) on the photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material and the kinetic fitting line when other conditions are the same. The molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material photocatalyst synthesized at different titanium source and silver source dosage ratios has a significant effect on the adsorption performance and photocatalytic degradation performance of SMZ. Figure 4 -b The results show that the photocatalytic degradation of SMZ by molecular imprinted Ag3PO4 / TiO2 photocatalytic film material is in good agreement with the first-order reaction kinetic model. The correlation coefficient R 2 Both are greater than 0.98. With the increase of AgNO3 dosage, the adsorption rate of SMZ by molecular imprinted Ag3PO4 / TiO2 photocatalytic film material under dark conditions and the photocatalytic degradation rate of SMZ under visible light both increase first and then decrease. When the volume ratio of titanium source to 1wt% silver nitrate solution is 1:4, the adsorption rate and photocatalytic degradation rate of SMZ by molecular imprinted Ag3PO4 / TiO2 photocatalytic film material reach the maximum, and its reaction rate constant K' is 1.34×10 -2 min -1 , the degradation rate reached the highest, which was 80.9%. When the volume ratio of titanium source to 1wt% silver nitrate solution was too small or too much, the dark adhesion performance and photocatalytic degradation performance of molecularly imprinted Ag3PO4 / TiO2 photocatalytic film material decreased. The reason is that when the amount of silver nitrate solution is small, as the amount increases, more Ag3PO4 is formed to form a heterojunction with TiO2, in which Ag + It helps to enhance the electron capture ability of TiO2, effectively inhibit the recombination rate of electron-hole pairs, and thus improve the photocatalytic degradation activity of SMZ; and the catalyst's ability to absorb photons is continuously enhanced as the doping amount increases. When the amount of silver nitrate solution is further increased, on the one hand, the excess Ag + A large amount of silver phosphate complexes will be formed, and the new phase produced will be deposited on the surface of TiO2 crystals to reduce its specific surface area, resulting in a decrease in the catalytic rate of molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials; on the other hand, excessive Ag + will become the recombination center of electron-hole pairs, because Ag + The doping of Ag will shorten the distance between the capture sites of TiO2 to capture carriers, thereby capturing a large number of electrons and holes. + It will become its recombination center, reducing its quantum efficiency and leading to reduced photocatalytic activity.

[0083] 3. The influence of the number of molecularly imprinted Ag3PO4 / TiO2 loading layers on the photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials.

[0084] Figure 5 The figure shows the effect of different loading layers on the photocatalytic degradation of SMZ by molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film materials and the kinetic fitting straight line diagram under the same other conditions. Figure 5 It can be seen that all the fitting lines conform to the pseudo-first-order kinetic equation, and the correlation coefficient R 2 The values ​​of K′ and K′ of the molecular imprinted Ag3PO4 / TiO2 photocatalytic film materials were all greater than 0.99, indicating that the photocatalytic reaction rate constant K′ value can better and intuitively reflect the photocatalytic degradation effect of the molecular imprinted Ag3PO4 / TiO2 photocatalytic film materials on SMZ. With the increase of the number of loading layers, the degradation rate constant K′ value of the molecular imprinted Ag3PO4 / TiO2 photocatalytic film materials on SMZ first increased and then decreased. When the number of loading layers was 2, the molecular imprinted Ag3PO4 / TiO2 photocatalytic film materials had poor catalytic activity, and the rate constant K′ value and degradation rate of SMZ were low, which were 1.0×10 -2 min -1 and 67%; with the increase of the number of loading layers, the K′ value and degradation rate increase accordingly. When the number of surface loading layers is 4, the rate constant K′ value is 1.27×10 -2 min -1 , the degradation rate reaches a maximum of 75%; when the number of loading layers is 8, the rate constant K′ value is 1.10×10 -2 min -1 , the degradation rate reached a maximum of 69%, which shows that when the number of surface loading layers is 4, the composite film has the best photocatalytic degradation effect of SMZ. This is because when the number of loading layers is small (less than 4 layers), as the number of loading layers increases, the MAT photocatalyst loading on the surface of the transparent carrier increases, and the formed composite film is more uniform, that is, the number of exposed photocatalytic particles on the surface increases and the dispersion is more uniform, covering a wide area, thereby increasing the effective photocatalytic area. When the light source irradiates the film, the photocatalyst is excited to produce more active oxidative free radicals, which effectively and fully contact with the SMZ target molecules in the solution, thereby improving the photocatalytic performance; but when the number of loading layers is too much, on the one hand, it will cause the MAT nanoparticles to be unable to be uniformly loaded on the limited transparent carrier surface, resulting in agglomeration, shielding the corresponding imprinted cavities and photocatalytic active sites, which is not conducive to the improvement of adsorption performance and photogenerated electron yield, resulting in a decrease in the photocatalytic activity of the composite film; on the other hand, too much loading will also cause light scattering, reduce the probability of absorbing photons, thereby reducing the amount of surface electron-hole pairs generated, and reducing the photodegradation efficiency.

[0085] Comparative Example 1

[0086] This comparative example provides a method for preparing a non-molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material, comprising the following steps:

[0087] 1. Dissolve 10 ml of butyl titanate and 4 ml of glacial acetic acid in 20 ml of anhydrous ethanol, stir at room temperature at 25 °C for 1 h to obtain a uniform and transparent yellow solution, which is recorded as liquid A; at room temperature, add 6 ml of anhydrous ethanol, 6 ml of glacial acetic acid, and 4 ml of distilled water into a 250 ml beaker, stir magnetically for 1 h to mix thoroughly, and place in a separating funnel for standby use, which is recorded as liquid B; under rapid stirring, slowly add liquid B to liquid A at a rate of 10 drops / min to obtain a colorless, uniform and transparent sol, and then add 40 ml of 1 wt% silver nitrate solution in turn. liquid and 40mL of 2wt% sodium phosphate solution, magnetically stirred for 60min, and then the pH value of the solution was adjusted to 2.5 to form liquid C; after continuing stirring for 3 hours, the white hydrogel solution was obtained, and the white gel was obtained after aging at room temperature for 12h, which was transferred to the lining of the reactor and hydrothermally reacted at 180°C for 20h. After naturally cooling to room temperature, the reaction products were collected and centrifuged and washed, washed with anhydrous ethanol and deionized water for 3 times each, and dried at 70°C to obtain non-molecularly imprinted Ag3PO4 / TiO2 (NAT) powder.

[0088] 2. Use detergent and distilled water to repeatedly clean the surface of a 250 mL cylindrical quartz glass tube for several times, wipe off water droplets with absorbent paper after cleaning; soak the surface of the quartz glass tube with a 1 mol / L NaOH solution for 3 hours, and rinse off the residual liquid with distilled water for several times; then soak the surface of the quartz glass tube with a 40% HF solution for 12 hours, and rinse off the residual liquid with distilled water for several times; finally, soak the quartz glass in an acetone solution, take it out after 4 hours, and rinse it again with distilled water. After the treatment is completed, move the quartz glass to an oven (90°C) for drying to obtain a pretreated quartz glass tube.

[0089] 3. Accurately weigh 1g NAT powder and 0.1g polyvinylpyrrolidone PVP-k30 in a 250mL beaker, add 150mL distilled water and stir magnetically for 30min, adjust the pH of the solution to 7.5 with HCl (0.1mol / L) and NaOH (1mol / L), stir magnetically for 15min to mix thoroughly, and finally place the solution in an ultrasonic cleaner for 30min to obtain a stable and uniform NAT sol.

[0090] 4. The prepared NAT sol was fully transferred to a 250 mL measuring cylinder, and the pretreated quartz glass tube was completely immersed in the measuring cylinder for 4 hours. Then, while ensuring that the quartz glass tube did not contact the inner wall of the measuring cylinder, it was taken out at a uniform speed and placed in an oven at 80°C for drying. The quartz glass tube was rotated horizontally and at a uniform speed until the NAT sol could be evenly and stably loaded on the outer surface of the quartz glass tube. The quartz glass tube was then dried for 3 hours until the sol was completely dried. The loading was completed once, and the number of loaded layers of non-molecularly imprinted Ag3PO4 / TiO2 was one layer. The soaking and drying steps were repeated once more, so that the number of loaded layers of non-molecularly imprinted Ag3PO4 / TiO2 was 2 layers, and the non-molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material was obtained.

[0091] The non-molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this comparative example was characterized by field emission scanning electron microscopy (FESEM) to obtain a SEM image, as shown in FIG. Figure 6 As shown. Figure 6 It can be seen that the NAT photocatalyst shown in the figure has Ag3PO4 particles with a size between 30 and 50 nm, mostly round or irregular polygonal, uniformly deposited on the surface of TiO2 particles, with good dispersion, but still inferior to the molecular imprinting Ag3PO4 / TiO2 photocatalytic thin film material with good dispersion, and lacks a pore structure and no obvious cavity, which is not conducive to the capture and catalytic degradation of the target substrate.

[0092] The non-molecular imprinted Ag3PO4 / TiO2 photocatalytic thin film material of this comparative example was tested according to the aforementioned photocatalytic degradation test, and the degradation rate was 58.4%.

[0093] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material for adsorption and degradation of sulfadimethoxine, characterized in that: The steps include: S1. The molecular template and titanium source are dissolved in a solvent to undergo a hydrolysis-condensation reaction, and then a silver source solution and a phosphate are added in sequence, stirred, and subjected to a hydrothermal reaction at 120-200°C for 16-24h, and the molecular template is removed by calcination to obtain molecularly imprinted Ag3PO4 / TiO2; S2. The molecularly imprinted Ag3PO4 / TiO2 is loaded on a transparent carrier to obtain the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material; In step S1, the molecular template is sulfadimethoxine, the molar ratio of the molecular template to the titanium source is (4-10):1; the volume ratio of the titanium source to the silver source solution is 1:(1-5); the titanium source is butyl titanate; the mass fraction of the silver source in the silver source solution is 0.8-1.2%; the silver source in the silver source solution is AgNO3; The number of loaded layers of the molecular imprinted Ag3PO4 / TiO2 in step S2 is 2 to 8 layers.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the molecular template to the titanium source in step S1 is (6-10):

1.

3. The preparation method according to claim 1, characterized in that: The stirring condition in step S1 is: stirring for 3 to 4 hours at a pH of 2 to 3.

4. The preparation method according to claim 1, characterized in that: The conditions of the hydrothermal reaction in step S1 are: reacting at 160-180° C. for 20-24 h.

5. The preparation method according to claim 1, characterized in that: The calcination conditions in step S1 are: calcination at 400-550° C. for 1.5-3 h.

6. The preparation method according to claim 1, characterized in that: The phosphate in step S1 is one or more of Na3PO4·12H2O, Na2HPO4·7H2O or NaH2PO4·2H2O.

7. The preparation method according to claim 1, characterized in that: The specific process of the loading in step S2 is: dispersing the molecular imprinted Ag3PO4 / TiO2 in a dispersing solvent to obtain a sol, immersing the transparent carrier in the sol, taking it out, and drying it to complete the loading.

8. A molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the molecularly imprinted Ag3PO4 / TiO2 photocatalytic thin film material according to claim 8 in the adsorption and degradation of sulfadimethoxine in food.

Citation Information

Patent Citations

  • A direct method for preparing molecularly imprinted TiO2 / WO3 composite photocatalysts with visible light response.

    CN102284284A

  • Preparation method and application of modified nano titanium dioxide photocatalyst

    CN113117704A

  • Molecularly imprinted photocatalytic material as well as preparation method and application thereof

    CN113578364A

  • Photocatalyst of TiO film for purifying water and its preparing process

    CN1390636A